Securing and Concealing Messages in the Edge Area of Digital Images Using Least Significant Bit Method and Blowfish Algorithm - Nur, Arviansyah; Supardi, Julian; Rachmatullah, M. Naufal (Fakultas Ilmu Komputer Universitas Sriwijaya, 2024)
The process of cryptography produces random text that can obscure a message, making it difficult for others to read. However, cryptography itself is still not strong enough to secure the message, so steganography is needed to conceal the existence of the message from the human eye. Besides hiding the message, another objective is to assess the impact of message embedding. In the process of encrypting and decrypting the message, the Blowfish algorithm is used, while message embedding utilizes the Least Significant Bit steganography, and edge detection is performed using the Canny algorithm. Through research conducted with the combination of cryptography and steganography, an excellent image is obtained with a PSNR value of 76.6932 and MSE of 0.0013 for a message length of 64 bytes. Meanwhile, visually, the results show a relatively similar appearance between the host image and the stego image.